Analisis Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Terhadap Penggunaan E-Money Sebagai Alat Pembayaran Parkir Di CSB Mall Kota Cirebon - Windi Aulia; Aan Jaelani; Moh. Mab’ruri Faozi (FEB Universitas Sultan Ageng Tirtayasa, 2025)
Public interest is one of the important aspects in consumer behavior that reflects interest and tendency in using a product. Electronic money is a relatively new payment instrument and is rarely used as a means of paying for parking. The existence of merchants who provide transactions using electronic money in Cirebon City is still limited, CSB Mall is one of the malls in Cirebon City that uses a parking payment system with electronic money. The purpose of this study was to analyze how the influence of ease of use, benefits and trust on public interest in using electronic money as a means of paying for parking at CSB Mall, Cirebon City. This study was conducted on visitors to CSB Mall, Cirebon City with a population of 8,833,000 people. The number of samples in this study was 100 visitors who were calculated using the Slovin formula and purposive sampling with a non-random sampling method. The respondent criteria in this study were visitors and users of electronic money (e-money) who had made parking transactions at CSB Mall, Cirebon City. The data analysis method used was quantitative research and multiple linear regression using SPSS 25.The results of this study indicate that the validity and reliability tests were declared valid and reliable. Partial hypothesis testing (t-test) shows that the variables of benefits and trust have a positive and significant effect on public interest in using e-money as a means of paying for parking at CSB Mall, Cirebon City, while the variable of ease of use has no significant effect. Then for the simultaneous test (f-test) shows that the variables of ease of use, benefits, and trust have a simultaneous and significant effect on the dependent variable of public interest in using electronic money (e-money) as a means of paying for parking for visitors to CSB Mall, Cirebon City.